A programme to treat chronic hepatitis B in Kiribati: progress and challenges - Lee, Alice Unah; Jackson, Kathy; Tekoaua, Rosemary; Lee, Caroline; Huntley, Margaret Sue; Hilmers, David Carl (Western Pacific Surveillance and Response, 2020)
Problem: Over 290 million people worldwide suffer from chronic hepatitis B (CHB), with the highest prevalence in the Pacific islands. Mortality attributable to this disease exceeds that from HIV, tuberculosis and malaria combined in this region.Context: CHB is a major health problem in the Pacific island nation of Kiribati. Medical care is complicated by vast expanses of ocean separating population centres in its constituent islands. Birth-dose hepatitis B immunization rates need improvement. High rates of obesity, metabolic syndrome, and co-infection with hepatitis B and hepatitis D in Kiribati make treatment less effective. Staff allocation, training and retention are difficult. Limited infrastructure creates challenges in training, communications, laboratory testing and record-keeping.Action: We have established a CHB treatment programme in Kiribati based on World Health Organization (WHO) guidelines and local needs. It includes direct patient care; laboratory, radiology and pharmacy support; public education; training; and data management. Thousands of individuals have been screened, and 845 hepatitis B-positive patients have had blood sent to Australia for molecular testing. Patient education pamphlets, medical training programmes and treatment protocols have been developed. Seventy-nine patients have started treatment. Regular onsite visits by technical experts are scheduled throughout the year.Lessons learnt and discussion: This is the first national CHB treatment programme established in the Pacific islands region. Unique challenges exist in Kiribati, as they do in each nation affected by CHB. Close engagement with local partners, knowledge of the barriers involved, flexibility, advocacy, and support from WHO and volunteer technical experts are key attributes of a successful treatment programme.